THE BOOK ABOUT KAITAG. Review on the book by A.O. Murtazaev "Kaitag in the VIII - first half of the XIX century (Study of political history and role in the system of political structures of the Nort-Caucasus)". - Makhachkala: "ALEF", 2015. - 490 p. - Aliev, B G; Inozemceva, E I (History, Archeology and Ethnography of the Caucasus, 2016)
-